Applications and therapeutic mechanisms of action of mesenchymal stem cells in radiation-induced lung injury - Shiying Niu; Yueying Zhang (Stem Cell Research & Therapy, 2021)
Abstract Radiation-induced lung injury (RILI) is one of the most common complications associated with radiotherapy, characterized by early-stage radiation pneumonia and subsequent radiation pulmonary fibrosis. However, effective therapeutic strategies for RILI are currently lacking. Recently, an increasing number of studies reported that mesenchymal stem cells (MSCs) can enhance the regeneration of damaged tissue, modulate the inflammatory response, reduce the levels of fibrotic cytokines and reactive oxygen species, and inhibit epithelial-mesenchymal transformation. Interestingly, MSCs can also exert immunosuppressive effects, which highlights a new potential therapeutic activity of MSCs for managing RILI. Here, we reviewed the potential applications and therapeutic mechanisms of action of MSCs in RILI, which will represent a good compendium of information for researchers in this field.